EVALUATING BUREAUCRATIC REFORM STRATEGIES FOR POVERTY REDUCTION IN THE IKN BUFFER ZONES OF EAST KALIMANTAN - Daryono, Daryono; Khaerani, Thalita Rifda; Utomo, Heryono Susilo; Aritonang, Melissa Monica; Sari, Novalin Delvia (International Journal of Cultural and Social Science, 2025)
Thematic Bureaucratic Reform was initiated to address the limited impact of previous reforms and to improve government effectiveness, efficiency, transparency, and accountability in tackling key issues, especially poverty alleviation. This study examines the implementation stages of the reform in the poverty alleviation focus area within the buffer zone of the Nusantara Capital City and identifies inhibiting factors. A descriptive qualitative method was employed, involving three stages: description, reduction, and selection. Data were gathered through interviews, observations, and focus group discussions. The findings show that local governments have initiated programs that help raise incomes and lower community expenses, contributing positively to poverty reduction efforts. However, technical and operational challenges—such as coordination gaps and limited resources—still hinder progress. The study underscores the need for strengthened implementation strategies and policy alignment to meet poverty reduction targets by 2024.